2020
DOI: 10.2337/db19-1239
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Adipocyte Becn1 Leads to Lipodystrophy and Metabolic Dysregulation

Abstract: Becn1/Beclin-1 is a core component of the class III phosphatidylinositol 3-kinase required for autophagosome formation and vesicular trafficking. Although Becn1 has been implicated in numerous diseases such as cancer, aging, and neurodegenerative disease, the role of Becn1 in white adipose tissue and related metabolic diseases remains elusive. In this study, we show that adipocyte-specific Becn1 knockout mice develop severe lipodystrophy, leading to adipose tissue inflammation, hepatic steatosis, and insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…BECN1 is a haploinsufficient tumor suppressor gene as a core component of the class III phosphatidylinositol 3-kinase that is involved in autophagosome formation and vesicular trafficking ( 37 ). It has been suggested that BECN1 was required for mitophagy completion, and suppressed mitophagy by BECN1 deficiency could cause aberrant mitochondria quality control in adipocyte to cause lipodystrophy and metabolic dysregulation ( 38 ). The qRT-PCR experiment results of MAP1LC3A (adjusted P -value = 1.30×10 -3 and log 2 (FC) = 0.71) and MAP1LC3B (adjusted P -value = 8.47×10 -4 and log 2 (FC) = 0.35) showed higher expression levels in the 40 mM oxamate treated groups than the non-treated groups after validations ( P -value < 0.01 after student’s t -test) ( Figure 3C ), which is consistent with the transcriptome results in the up-regulated status ( Supplementary File 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…BECN1 is a haploinsufficient tumor suppressor gene as a core component of the class III phosphatidylinositol 3-kinase that is involved in autophagosome formation and vesicular trafficking ( 37 ). It has been suggested that BECN1 was required for mitophagy completion, and suppressed mitophagy by BECN1 deficiency could cause aberrant mitochondria quality control in adipocyte to cause lipodystrophy and metabolic dysregulation ( 38 ). The qRT-PCR experiment results of MAP1LC3A (adjusted P -value = 1.30×10 -3 and log 2 (FC) = 0.71) and MAP1LC3B (adjusted P -value = 8.47×10 -4 and log 2 (FC) = 0.35) showed higher expression levels in the 40 mM oxamate treated groups than the non-treated groups after validations ( P -value < 0.01 after student’s t -test) ( Figure 3C ), which is consistent with the transcriptome results in the up-regulated status ( Supplementary File 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, early studies using adipose-specific deletion of autophagy-related genes show that mice accumulate more mitochondria in WAT, producing a browning of WAT phenotype with reduced body weight and WAT mass (Baerga et al, 2009; Zhang et al, 2009). Among the autophagy pathway, BECN1 is a scaffolding protein that is key for the initiation of autophagosome biogenesis (He and Levine, 2010), and therefore, we can target and activate autophagy at early steps; the role of BECN1 in adipose tissue has been recently appreciated: adipocyte-specific BECN1 knockout mice develop severe lipodystrophy and metabolic dysfunctions (Jin et al, 2021; Son et al, 2020). However, it is not clear what role BECN1 plays in UCP1 + cells and whether BECN1 mediates beige activity downstream of the Cdkn2a pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of Atg7 deletion in mature adipocytes remains to be determined, other studies have shown that autophagy also plays an important role in the regulation of post-developmental functions and homeostasis of mature adipocytes. Different from KO of Atg7 during adipose development stages, adipocyte-specific KO of Becn1 during adulthood increases adipose tissue inflammation, ER stress and apoptosis, and decreases insulin sensitivity (Jin et al, 2021). Similarly, post-developmental adipose-specific deletion of Atg3 or Atg16L1 leads to dysfunctional mitochondria accumulation followed by increased lipid peroxides in adipose tissue, although fat mass and body weight appear to be unaffected.…”
Section: Regulation Of Tissue Development and Homeostasis Adipose Tis...mentioning
confidence: 96%